Sara E. Ellis Nilsson, Creating Holy People and Places on the Periphery. A Study of the Emergences of Cults of Native Saints in the Ecclesiastical Provinces of Lund and Uppsala from the Eleventh to the Thirteenth Centuries, Gothenburg: University of Gothenburg 2015 - Kirsi Salonen (Umeå University & The Royal Skyttean Society, 2022)
Väitöskirjan arvostelu